Regionalisation, globalisation and the emerging world economy : organisation, the regional integration agreements and European Union - Lima, Maria Antonina (2022)
ln this paper, an attempt has firstly been made to characterize two main tendencies emerging in the world economy during the eighties and the nineties: regionalisation and globalisation(l). Then, that tendency has been analysed through the development of the International Trade System, in particular after the conclusion of the Uruguay Round (1986- 1993), the setting up of the World Trade Organization (WTO) and the simultaneous proliferation of regional integration agreements (RIAs) ali over the world (II). Finally, a general view of "European regionalism" is presented, emphasizing the double movement towards the increase of European integration (European internal market and the economic and monetary union) and the new enlargements to the Eastern and the Southern frontiers (the Eastern European countries and Mediterranean countries) (III).